Barriers and facilitators to the implementation of audio-recordings and question prompt lists in cancer care consultations: A qualitative study. Issue 6 (June 2017) - Moloczij, Natasha; Krishnasamy, Mei; Butow, Phyllis; Hack, Thomas F.; Stafford, Lesley; Jefford, Michael; Schofield, Penelope
Highlights: Question prompt lists and consultation audio-recordings can assist cancer patients in understanding and recalling information. Clinicians and hospital administrators are supportive of integrating strategies into usual care. Use of a strategy should be driven by patient preference. Many individual, relational, system, resourcing and medico-legal considerations are identified. Identifying and addressing practical implications prior to clinical implementation is essential. Abstract: Objective: Question prompt lists (QPLs ) and consultation audio-recordings (CARs) are two communication strategies that can assist cancer patients in understanding and recalling information. We aimed to explore clinician and organisational barriers and facilitators to implementing QPLs and CARs into usual care. Methods: Semi-structured interviews with twenty clinicians and senior hospital administrators, recruited from four hospitals. Interviews were recorded, transcribed verbatim and thematic descriptive analysis was utilised. Results: CARs and QPLs are to some degree already being initiated by patients but not embedded in usual care. Systematic use should be driven by patient preference. Successful implementation will depend on minimal burden to clinical environments and feedback about patient use. CARs concerns included: medico-legal issues, ability of the CAR to be shared beyond the consultation, and recording and storage logistics within existing medical record systems. QPLs issues included: applicability of the QPLs, ensuring patients who might benefit from QPL's are able to access them, and limited use when there are other existing communication strategies. Conclusions: While CARs and QPLs are beneficial for patients, there are important individual, system and medico-legal considerations regarding usual care. Practice implications: Identifying and addressing practical implications of CARs and QPLs prior to clinical implementation is essential.